A novel type-2 innate lymphoid cell-based immunotherapy for cancer - Saranchova, Iryna; Xia, Clara Wenjing; Besoiu, Stephanie; Finkel, Pablo L.; Ellis, Samantha L. S.; Kari, Suresh; Munro, Lonna; Pfeifer, Cheryl G.; Fazli, Ladan; Gleave, Martin E.; Jefferies, Wilfred A. (Frontiers in Immunology, 2024)
Cell-based cancer immunotherapy has achieved significant advancements, providing a source of hope for cancer patients. Notwithstanding the considerable progress in cell-based immunotherapy, the persistently low response rates and the exorbitant costs associated with their implementation still present a formidable challenge in clinical settings. In the landscape of cell-based cancer immunotherapies, an uncharted territory involves Type 2 innate lymphoid cells (ILC2s) and interleukin-33 (IL-33) which promotes ILC2 functionality, recognized for their inherent ability to enhance immune responses. Recent discoveries regarding their role in actuating cytolytic T lymphocyte responses, including curbing tumor growth rates and hindering metastasis, have added a new dimension to our understanding of the IL-33/ILC2 axis. These recent insights may hold significant promise for ILC2 cell-based immunotherapy. Nevertheless, the prospect of adoptively transferring ILC2s to confer immune protection against tumors has yet to be investigated. The present study addresses this hypothesis, revealing that ILC2s isolated from the lungs of tumor-bearing mice, and tumor infiltrating ILC2s when adoptively transferred after tumor establishment at a ratio of one ILC2 per sixty tumor cells, leads to an influx of tumor infiltrating CD4+ and CD8+ T lymphocytes as well as tumor infiltrating eosinophils resulting in a remarkable reduction in tumor growth. Moreover, we find that post-adoptive transfer of ILC2s, the number of tumor infiltrating ILC2s is inversely proportional to tumor size. Finally, we find corollaries of the IL-33/ILC2 axis enhancing the infiltration of eosinophils in human prostate carcinomas patients' expressing high levels of IL-33 versus those expressing low levels of IL-33. Our results underscore the heightened efficacy of adoptively transferred ILC2s compared to alternative approaches, revealing an approximately one hundred fifty-fold superiority on a cell-per-cell basis over CAR T-cells in the specific targeting and elimination of tumors within the same experimental model. Overall, this study demonstrates the functional significance of ILC2s in cancer immunosurveillance and provides the proof of concept of the potential utility of ILC2 cell-based cancer immunotherapies.